Geodiversity decreases shrub mortality and increases ecosystem tolerance to droughts and climate change. Issue 13 (25th May 2018) - Stavi, Ilan; Rachmilevitch, Shimon; Hjazin, Amgad; Yizhaq, Hezi
Abstract: Mass mortality of shrubs, especially the Noaea mucronata species, has been observed in the semi‐arid Negev of Israel since the early twenty‐first century. This has followed a long‐term drought episode, and suggests a hysteresis‐like effect. However, recent studies have revealed that the mortality has been varied across the region. Therefore, we assessed the depth and stoniness of the soil profile, in homogeneous and heterogeneous hillslopes. Then, we studied the volumetric moisture content during two consecutive growing seasons, in the topsoil of shrubby patches and of inter‐shrub spaces in these hillslopes. The study shows that geodiversity – characterized by shallow soil, a high content of stones in the soil, and a high cover of rock fragment on the surface – reduced shrub mortality. This was attributed to the soil moisture content, which was considerably greater in the heterogeneous hillslopes, than that in the homogeneous hillslopes. It is proposed that the shallow soil halted the growth of herbaceous vegetation in the inter‐shrub spaces of the heterogeneous hillslopes. Therefore, under rainstorms, this hillslope configuration results in considerable generation of overland water flow in the inter‐shrub spaces. The water accumulates in the shrubby patches, allowing them to thrive, even during long‐term dry episodes. In hillslopes with a deep soil layer, no stoniness in the soil profile, and no cover of rock fragments, the herbaceous vegetation is well developed, covering a considerable share of the inter‐shrub spaces. This negates runoff formation and source–sink relations, limiting water availability for the shrubs, and resulting in their mass mortality. Despite no direct pastoral value for livestock, the shrubs play an important role in overall ecosystem functioning. This is due to their capacity to transect hydraulic connectivity, and negate ecosystem collapse. We propose a conceptual model for demonstrating the role played by geodiversity in alleviating drought stress in drylands. Copyright © 2018 John Wiley & Sons, Ltd. Abstract : This study reveals a positive effect of geodiversity on spatial redistribution of water, with the formation of source–sink relations between inter‐shrub spaces and shrubs, with the resultant thriving of shrubs under prolonged droughts. At the same time, the absence of source–sink relations in low‐geodiversity hillslopes negate shrub survival under increased aridity conditions. Despite the little consumption of shrubs by livestock animals, their role in transecting the hillslope makes them crucial in sustaining geo‐ecosystem functioning and negating land degradation.